Análise crítica sobre a prática da vaquejada e a sua constitucionalização pela PEC 50/2016 - Lima, Luana Priscila de (Universidade Federal Rural do Semi-Árido, 2017)
The vaquejada is considered as a cultural tradition and recognized as a sport throughout Brazil, this recognition adds an economic purpose, moving millions in money every year. Unfortunately, the vaquejada is based on the overthrow of the oxen in the lane, causing in these animals several evils, such as: fractures, dislocations, among others. Recently, in October 2016, the STF recognized the unconstitutionality of the vaquejada, through ADI 4983, since such a practice would be intrinsically cruel to the animals. On the other hand, this year, the Senate approved the PEC nº 50, assuring the right of realizations of events of this nature and recognizing it as cultural patrimony. Based on the current high content of the theme, it is essential to perform the critical analysis of the vaquejada practice and its consequent constitutionalisation, rationalizing about its causes and consequences.
Artigo Acadêmico
Keywords: Animais; Cultura; Vaquejada; Inconstitucionalidade; Crueldade; Animals; Culture; Vaquejada; Unconstitutionality; Cruelty; CIENCIAS SOCIAIS APLICADAS::DIREITO